The magic nation thing - Snyder, Zilpha Keatley (Delacorte Press, 2005)
Although twelve-year-old Abby has always tried to deny that she has some kind of weird psychic power, she takes advantage of it to help her mother, a struggling private investigator, and, more importantly, to find her best friend's little brother when he goes missing at a ski resort.